ORGANIZATIONAL DESIGN OF THE PERSONNEL MANAGEMENT SYSTEM OF AN INTERMEDIARY ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the theoretical aspects of designing an adequate organizational structure of personnel management of an intermediary enterprise, the use of the most appropriate approaches, principles and methods of structure formation in the process of supplying goods and products of industrial and technical purpose to any consumers in the region.The article defines the essence of the commercial intermediary firm as the most widespread link in the commodity market infrastructure and the essence of the organizational design of the personnel management system of intermediary enterprises. The main components of the goal of organizational design of personnel management were evaluated. The main characteristics of the personnel management system of the intermediary enterprise were studied.The activity of the transition to the complex organizational development of commercial mediation as the most effective and modern advanced foreign experience is considered. On the basis of research, the organizational structure of personnel management of an intermediary enterprise is given.
Keywords: organizational design of personnel management system, personnel management, intermediary enterprise, organizational structure of personnel management.